The Effect Of 8 Repetition Badminton Footwork Training In Increasing Leg Muscle Flexibility And Endurance - Astrawan, I Putu; I Made Dhita Prianthara; Komang Tri Adi Suparwati; Made Ganggas Dwiatmaja Empuaji (UNIB Press, 2024)
The basic movements of badminton are directed at footwork. The research aims to prove the effect of 8 repetitions of footwork training on flexibility and leg muscle endurance. Experimental research with a pre and post test control group design. The research sample consisted of 30 people divided into 2 groups. KI footwork training 8 repetitions and KII control. The results of the data normality and homogeneity tests show that the data distribution is normal and homogeneous. The test results for differences in mean flexibility and endurance of leg muscles using the t-paired test between groups were significantly different (p<0.05). KI flexibility, the pre test mean 3.33 and the post test 11.93, the difference 8.60. KII, the pre test mean 3.86 and the post test 5.06, a difference 1.20. In KI leg muscle endurance, the pre test average 16.86 and the post test 28.53, the difference 11.66. KII, mean pre test 17.06 and post test 18.33, difference 1.26. It was concluded that 8 repetitions of badminton footwork training increased flexibility and leg muscle endurance.